Orientasi Keilmuan Dakwah pada Jurusan KPI Fakultas Dakwah IAIN Imam Bonjol - Bukhari, Bukhari (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
The study of preaching in Islamic Broadcasting Communication of Preaching Faculty IAIN Imam Padang  has aims to assess the existence of subject knowledge and how urgency preaching and organizing the next course in line with the times. Until Islamic Broadcasting Communications degree alumni, faculty and alumni in particular is generally expected to be able to compete in the world of work. The important studies include: 1. existence of subjects offered now, 2. Issues missionary at present, 3. Missionary challenge in the development of the global age, 4. Missionary knowledge future orientation, and 5. Offer courses that are relevant to the times